Cognitive approach to distance learning materials preparation adapted to asynchronous mode - Kushtina, Emma; Rozewski, Przemyslaw (Journal of Business Economics and Management, 2003)
The authors discuss the method of designing the distance learning didactic materials for the asynchronous mode. The approach is based on the modular structure of the fundamental knowledge. The new role of the teacher is being discussed as well as its impact on the didactic materials’ structure and content. The paper introduces the knowledge representation model designed to meet the requirements of theoretical knowledge presentation in a selected domain using the Learning Object concept.First Published Online: 14 Oct 2010